New species of Horistonotus Candèze from Brazil (Coleoptera, Elateridae, Cardiophorinae) - Casari, Sônia A. (Zootaxa, 2011)
Eight species of Horistonotus Candèze (1860), from states of Alagoas and Sergipe, are described and illustrated and a provisional identification key for all Brazilian species of this genus is provided. The described species were collected in the Caatinga, semi-desert tropical woodland, in the Northeastern Region of Brazil. The genus Horistonotus is very numerous with more than a hundred species, distributed throughout of North, Central and South America.